2021
DOI: 10.1051/parasite/2021078
|View full text |Cite
|
Sign up to set email alerts
|

Point of care colourimetric and lateral flow LAMP assay for the detection of Haemonchus contortus in ruminant faecal samples

Abstract: In this study, we present an optimised colourimetric and a lateral flow LAMP assay for the detection of Haemonchus contortus in small ruminant faecal samples. Using a previously published LAMP primer set, we made use of commercially available colourimetric LAMP and lateral flow kits and combined this into an optimised diagnostic assay which was then tested on field faecal samples from Eastern and South-Eastern Hungary as well as a pure H. contortus egg faecal sample from Košice, Slovakia. Both assays showed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Positive LAMP signal is typically visualized with the SYBR dye, turbidimeter or UV light, presenting certain limitations for on-site testing ( 54 , 55 ). Lateral flow technology was also demonstrated to have diagnostic potential to detect LAMP amplicons ( 23 ). In contrast, our ABSTA testing approach results in glucose readouts, which are stable and highly compatible with commercially available handheld glucometers to help shorten the time-to-results, as demonstrated in a previous study ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive LAMP signal is typically visualized with the SYBR dye, turbidimeter or UV light, presenting certain limitations for on-site testing ( 54 , 55 ). Lateral flow technology was also demonstrated to have diagnostic potential to detect LAMP amplicons ( 23 ). In contrast, our ABSTA testing approach results in glucose readouts, which are stable and highly compatible with commercially available handheld glucometers to help shorten the time-to-results, as demonstrated in a previous study ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, utilizing loop-mediated isothermal amplification (LAMP) as a component of on-farm diagnostics could be more promising, given its ability to detect genetic targets in under 30 min and higher sensitivity than PCR with a more simplified sample preparation ( 18 20 ). Positive results can be observed by changes in fluorescence or turbidity, and lateral flow assay ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of recognized PCR inhibitors such as calcium, fat, or protein in milk necessitates using specific DNA extraction techniques to ensure high-quality findings. Alternative to regular PCR and quantitative (qPCR) procedures, loop-mediated isothermal amplification (LAMP) has been described as a promising molecular tool for quick on-farm diagnostics [ 161 , 162 ] and food pathogen detection [ 163 , 164 , 165 , 166 , 167 ]. This approach is quicker than PCR, less costly, highly selective for the target sequence, and requires less template quality and complicated apparatus.…”
Section: On-farm and Lab Methods For Monitoring Udder Health And Milk...mentioning
confidence: 99%
“…Babják et al found that the in vitro egg hatch test can accurately estimate in vivo efficacy following treatment of H. contortus infections with benzimidazoles in goats and that it also reflects the percentage of resistance alleles in the parasite population [ 1 ]. Khangembam et al present an optimised LAMP assay for the detection of H. contortus in small ruminant faecal samples [ 9 ]. Both studies are an important step towards quicker and more cost-effective diagnosis of GIN infections (in this case H. contortus ) and their resistance status.…”
mentioning
confidence: 99%